Comparisons of Turf‐Type Bahiagrass (Paspalum notatum Flügge) Lines for Root and Shoot Traits under Various Nitrogen Regimes. Issue 1 (19th October 2017) - Pereira, Mateus C.; Rios, Esteban F.; Kenworthy, Kevin E.; Quesenberry, Kenneth H.; Blount, Ann; Erickson, John; Altpeter, Fredy; Munoz, Patricio
Abstract : Water and fertilizer regulations in Florida have created a market for low‐maintenance grasses. The objectives of this study were to compare rooting and turf performance of three selected turf‐type bahiagrass lines ('M36', 'WEMS12', and 'FLDW51'), in comparison with 'Wilmington' and 'Argentine' bahiagrass, and 'Floratam' St. Augustinegrass, grown under three nitrogen (N) rates (49, 98, and 196 kg N ha −1 ). The experiment was conducted during the summer and fall 2014 in a greenhouse located at the Genetics and Physiology Agronomy Unit, University of Florida, Gainesville, FL, and arranged as a randomized complete block design with four replications. Positive correlations were found between biomass and rooting traits, and both were negatively correlated with shoot and root crude protein. Coarse leaf texture was positively correlated with higher biomass yield but was negatively correlated with crude protein, number of nodes, and chlorophyll content. Cluster analysis based on principal component analysis 1 (51% explained variance) indicated two genotype groupings. Wilmington, WEMS12, and FLDW51 were grouped closely to crude protein, number of nodes, and chlorophyll content, whereas Floratam, Argentine, and M36 were grouped near leaf texture, biomass, and rooting traits. Principal component analysis 2 (18% explained variance) indicated that M36 and Wilmington were grouped closely to leaf length, rhizome size, root to shoot biomass, and crude protein ratios. The three experimental lines and Wilmington exhibited darker green color, had better color retention, and had more nodes per rhizome, and WEMS12 and FLDW51 had narrower leaves. Higher N rates induced higher chlorophyll content and crude protein. Floratam, Argentine, and M36 produced higher biomass yields and exhibited more vigorous root parameters. The improved turf attributes exhibited by these selected lines should be further evaluated for persistence under limited input field regimes.